Metodologi Pengajaran Qira'at Sab‘ah Studi Observasi di Pondok Pesantren Yanbu‘ul Qur'an dan Dar Al-Qur'an - Urwah, Urwah (SUHUF, 2012)
Islamic Boarding School (pesantren) Yanbu'ul Qur'an and the Dar Al-Qur'an of Cirebon are two boarding schools that are still continuing to teach the seven ways of reciting the Holy QurÃ¢â‚¬â„¢an (al-QirÃ„ÂÃ¢â‚¬â„¢Ã„Ât as-Sab'). Both have similarities and differences in teaching that method. This research will explain the method and systematic teaching of the seven ways of reciting the Holy QurÃ¢â‚¬â„¢an using socio-historical analysis approach. At the Islamic boarding school of Yanbu'ul Qur'an, tahfizul Qur'an (learning the QurÃ¢â‚¬â„¢an by heart) is one of the requirements that the students of the QiraÃ¢â‚¬â„¢at must have, because theÃ‚Â  talaqqiÃ‚Â  (the process of learning the QurÃ¢â‚¬â„¢an by heart by meeting face to face with the supervisor) is conducted by the way of the unseen (bil-gaib) and face to face. While at the Islamic boarding school of Dar Al-Qur'an of Cirebon, tahfizul QurÃ¢â‚¬â„¢an is not required because the process is conducted through the way calledÃ‚Â  talaqqi bin-naÃ‚Â§arÃ‚Â  (seeing the Qur'an), and is conducted in groups.